Comparative Analysis of Conventional and Islamic Banking: The Case of Bakhtar Bank Transforming into Islamic Bank of Afghanistan - Erdal ARSLAN; Ali BORA; Abdul Hasib AMANAT (Yönetim ve Ekonomi, 2020)
This article examines the financial performance of the Islamic Bank of Afghanistan after it transformed its form of banking from traditional Bakhtar Bank to Islamic Bank. in order to know whether or not there are significant differences in banks’ financial performance. We conducted the financial ratio analysis on audited financial statements of the bank from 2009 to 2019. As a result of the financial ratio analysis, we found that the bank’s financial performance has significantly improved from different perspectives namely return on assets, return on equities, liquidity, solvency, and leverage ratios have respectively increased by 0.005, 0.09, 1.69, 0.009, and 8.3 percent. In conclusion, the financial performance of Islamic bank of Afghanistan is considered superior compared to Bakhtar banks’ performance and Islamic Banking is considered favorable and successful in Afghanistan compared to Traditional banking.